PENGARUH PENERAPAN STRATEGI PEMODELAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VII SMPN 8 PAMEKASAN - Rosa Agustina Sari Rosa; Ach. Sya'roni (Dewan Pendidikan Pamekasan, 2022)
There are two issues that are the main studies in this study, first, Is the Effect of The Application of The Strategy of Learning To Student Learning On The Motivation of Learning Students in The Subjects of Islamic Religious Education in SMPN 8 Pamekasan?, secondly How Much Influence of Modeling Learning Strategies On Student Learning Motivation Of Islamic Religious Education Subjects in SMPN 8 Pamekasan. This research approach uses a quantitative approach, with a correlational type. The instruments used in data collection are questionnaires, interviews, observations and documentation. The results showed that: 1). There is an effect of The Application of Modeling Learning Strategies On Student Learning Motivation Of Islamic Religious Education Subjects in SMPN 8 Pamekasan. This is evident from the results of the analysis of data obtained at 0.87 out of 30 samples. This figure turns out to be greater than the price of the